Effect of Defatted Coconut Flour on Rabbit Growth - Acosta-Acosta, Yanixi; La-O-Michel, Ángel Luis; Valdivié-Navarro, Manuel; Maceo-Martínez, Anabel; Acosta-Ramos, Euler; Betancourt-Santos, Nelson Nixon; Villalón-Moracen, Yudelkis; Hechavarría-Riviaux, Suset (Universidad Pedagógica y Tecnológica de Colombia, 2019)
To evaluate the influence of defatted coconut flour (HCD) on the productive performance and yield to the carcass for growing rabbits, five diets were elaborated with increasing levels of this (0, 10, 20, 30 and 40 %), which were supplied to 130 animals of the Chinchilla breed, with a completely randomized design. The initial and final live weights, average daily gain, feed consumption, feed conversion, yield to the carcass and its valuable cuts were determined. The experimental period was 78 days. The final live weight of the animals during the fattening cycle was between 2060 and 2242 g/animal, in all cases above 2000 g which is the one established for the slaughter of the animals, the mean weight gain oscillated between 25.4 and 28.4. The inclusion of defatted coconut meal in the diet up to 40 % did not affect the yield to the carcass, its average values ​​ranged between 49.72 and 53.5 %. The results indicate that the rabbits made an adequate absorption of the nutrients when using defatted coconut flour for their growth, in addition the economic performance of the production system is improved.